Eksistensi Passompe’ di Daerah Perantauan - Hj. Suharty Roslan (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT The objective of this research is to describe and to analyze the form of existence and cultural mission of the migrant community (Businesses Ethnic) to occupya territory. The results showed that the existence of the migrant community could be seen from decision and choice they made in line with the occupation and settlement. Occupation preferences were performed by searching for available opportunities of informal sector in the urban area. The choice of occupation influences a selection of the settlement area. Settlement preferences of the migrants followed an expansion of shopping center at the center of city, in economy market sector. Tendency of the migrants to stay in the migration area and to view it as the permanent dwelling was the characteristic of permanent migration. This tendency was consistent with the cultural mission of the migrants based on the territory expansion. For the migrants, the migration area ideally becomes a part of their homes. This strategy made the migrants take more emphasis on the migration area than their original areas. Success and failure of the migrants could be measured by to which extent they could meet their mission of migration culture. Key Word: pasompe’ existence, culture mission